The normalisation of body regulation and monitoring practices in elite sport: a discursive analysis of news delivery sequences during skinfold testing - Cosh, S.; Crabb, S.; Kettler, L.; LeCouteur, A.; Tully, P. J. (Qualitative Research in Sport, Exercise and Health, 2015)
Prevalence of disordered eating is higher in athlete populations than in the general population. This paper explores the sociocultural context within which athletes are vulnerable to poor health behaviours and potentially poor mental health. Within sport settings, dominant ideals of body regulation and self-surveillance are normalised and leave athletes vulnerable to eating disorders. This paper explores how such ideals and understandings around the body are reproduced within the sporting environment during everyday interactions and how body regulatory practices come to be normalised. This paper draws on discursive psychology, informed by conversation analysis, to examine the news delivery sequences of 40 interactions occurring between elite athletes and sport staff during routine practices of body composition testing taking place in an Australian sport institute network. Through the news delivery sequences of body composition testing scores, practices of body regulation come to be normalised by both athletes and sport staff. Moreover, athletes are positioned as needing continually to improve, thus, (re)producing dominant notions of body regulation as requiring athletes` self-discipline and surveillance. Discursive practices occurring in sport settings can leave athletes at increased risk of developing unhealthy eating and exercising behaviours and disordered eating. Implications for practice for sport staff are